Data-based condition assessment of a T-beam bridge with orthotropic plate using strain measurements ... - Kimpeler, Stefan; Geers, Thorben; Hoffmeister, Benno (RWTH Aachen University, 2024)
NORDIC STEEL 2024 : the 15th Nordic Steel Construction Conference, June 26-28, 2024, Luleå, Sweden 15. Nordic Steel Construction Conference, Nordic Steel 2024, Luleå, Sweden, 26 Jun 2024 - 28 Jun 2024; [Stockholm] : The Swedish Institute of Steel Construction 1-10 (2024). doi:10.5281/ZENODO.11453277 ... : Published by The Swedish Institute of Steel Construction, [Stockholm] ...